Dinamika Fungsi Kota Lasem dalam Perkembangan Wilayah - Pramita Musonniva; Jawoto Sih Setyono (Teknik PWK (Perencanaan Wilayah Kota), 2020)
Small town is a low-order center in the urban hierarchy that has a vital function in the development process. Cities that have more diverse functions are considered able to develop faster than cities that only have a single function. The dynamics of urban development can occur along with the times. Small cities can experience significant stagnation or even degradation when they are unable to adjust to the changing times. Lasem is an old city that was once the center of the duchy and important trade in the northern coastal region. However, since the transfer of the power center to the City of Rembang and Lasem has been reduced to the status of a Subdistrict City, the development of Lasem City has stagnated gradually. The purpose of this study was to determine the dynamics function of the Lasem City in regional development. The results obtained from this study are Lasem City experiencing dynamics in several city functions. The city of Lasem experiences dynamics of diverse city functions, in some functions it has increased but on the other hand it has stagnated and even degraded development. The dynamics that occur between one city function and another are interrelated. The city of Lasem should be able to develop more rapidly than it is now, because it already has the power of its initial growth factor.